Салтівські пам’ятки Харківщини в розвідках 1949 р. І. П. Костюченка - Лаптєв, О. О. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryA. Laptev. Saltiv Monument Sites of Kharkov Region in the Explorations of I. Kostyuchenko at 1949The work is devoted to explorations in Kharkiv region at 1949. As a result of the work implemented by Kyiv University’s student I. Kostyuchenko 42 settlements were inspected. 30 of these settlements contained materials of Saltiv archaeological culture. Subsequently a lot of settlements have been discovered again, but some information was lost. According to the field materials (diary, inventory, receipts of collected materials’ points) the data about location the settlements contained Saltiv materials are summarized. This data are supplemented by history of monuments’ researches. Excerpts from field inventory are attached to the work. There is made an attempt to map these settlements.Key words: I. Kostyuchenko, Kharkiv region, explorations, Saltiv archaeological culture.